Research of Cloud Computing-Based Solution and Key Technical Implementation for Medium-Sized and Small Enterprises - Guoping Liu; Yanbing Zheng (Dianxin kexue)
It was still in the stage of exploration and experiment at home and abroad on how to unify the platform service, broadband network and diverse terminals to provide the integrated services although the cloud service mode accorded with the need of the medium-sized and small enterprises on the information development. A solution based on the cloud, pipeline and terminal architecture was proposed on the basis of the requirement analysis for the medium-sized and small enterprises. The overall framework, the technical architecture and the product hierarchy were put forward. The key implementation for the enterprise resource pool, virtualized application deployment and the cloud service security were discussed from the technical view and the practicing deployment architecture and its state of the art were provided.